The relationship of stress levels, nutritional status and physical activity with menstrual cycle disorders - Malinda Lutviani; Ni'mal Baroya; Ruly Bahyu Antika (Universitas 'Aisyiyah Yogyakarta, 2023)
Menstrual cycle disorders are abnormal uterine bleeding occurring in women of productive age and impact infertility. This study aims to analyze the relationship between stress levels, nutritional status, and physical activity with menstrual cycle disorders in female students of the Jember University public health study program. This research is quantitative research with a Cross-sectional design. The study population is active female Public Health Study Program students, University of Jember batch 2016-2020. The number of samples was 141 female students. Data collection using questionnaire filling through Google form sent to respondents. The collected data was then analyzed bivariate using Chi-Square and multivariate analysis using logistic regression. The results showed that 53% of female students experience menstrual cycle disorders. Stress level (OR 14.2; CI 5.10-38.77) and physical activity (OR 29.10; CI 9.20-92.10) are factors associated with menstrual cycle disruption in female college students. Female students with heavy stress levels and heavy physical activity can increase the risk of menstrual cycle disorders.